Decoupled Visual Servoing Control of a 7-DOF Robot Manipulator for an Onboard Monocular Vision System - Tejada-Begazo, Maria; Barrios-Aranibar, Dennis (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Robotic arms have been developed over several years, and various manipulators have been created for different tasks and workspaces. Consequently, the control system depends on the structure of the robotic arm (number, position, and type of joints and sensors). Therefore, a control system for a 7-degree-of-freedom manipulator arm with monocular vision at the wrist is proposed. The objective of this approach is a control system for tracking a target. The ‘eye-in-hand’ visual servomotor structure, a system where the camera is mounted on the robot’s end effector, is used to perceive and track a 3 cm diameter sphere. It should be noted that the robot only perceives a two-dimensional view of the environment, so a practical solution is proposed. A ‘divide and conquer’ strategy is used, in which the robot performs decoupled movements in two perpendicular planes, which are interleaved to create a smooth trajectory. Perception, forward kinematics, and proposed tests have been performed.